2009
DOI: 10.1590/s0102-05362009000400027
|View full text |Cite
|
Sign up to set email alerts
|

Espaçamento entre plantas e cachos por haste no tutoramento vertical do tomateiro

Abstract: O presente trabalho objetivou avaliar o efeito do espaçamento entre plantas e do número de cachos por haste sobre a produtividade e a qualidade de frutos do tomateiro conduzido no método de tutoramento vertical com fitilho. Experimentos foram conduzidos nas safras 2006/07 e 2007/08, na Epagri-Estação Experimental de Caçador-SC. Os tratamentos consistiram da combinação de três espaçamentos entre plantas (30, 45 e 60 cm), quatro alturas de desponta das plantas (sem desponta, cinco, sete e nove cachos por haste) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
10

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 4 publications
0
5
0
10
Order By: Relevance
“…Decreases in fruit quality (fruit grading and mass) related to increases in planting density are well described in literature for tomatoes (Azevedo et al, 2010;Wamser et al, 2009Wamser et al, , 2012 and are due to competition between plants (Papadopoulos & Pararajasingham, …”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Decreases in fruit quality (fruit grading and mass) related to increases in planting density are well described in literature for tomatoes (Azevedo et al, 2010;Wamser et al, 2009Wamser et al, , 2012 and are due to competition between plants (Papadopoulos & Pararajasingham, …”
Section: Resultsmentioning
confidence: 93%
“…Data adjustments resulted in linear models and, therefore, no maximum technical efficiency was reached within the planting density range studied. Effects of planting density on increasing tomato yield are well described in literature (Azevedo et al, 2010;Wamser et al, 2009Wamser et al, , 2012. Nevertheless, determination of the optimum density, in which maximum marketable fruit yield would be reached, has been receiving little attention.…”
Section: Resultsmentioning
confidence: 99%
“…According to Gebologlu and Sagllam (2002), when the density of plants per unit area increases, it is likely to reach a point at which plants compete for essential growth factors such as nutrients, light and water, reducing their productive capacity. Some authors have observed a reduction in fruit productivity with spacing elevation in some vegetables, such as tomato (Wamser et al, 2009), maxixe (Oliveira et al, 2010) and okra (Sediyama et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Por sua importância, a cultura do tomateiro tem sido muito estudada, especialmente no que diz respeito ao aumento da produtividade (Marim et al, 2005;Guimarães et al, 2007;Guimarães et al 2008;Charlo et al 2009;Wamser et al 2009) e à obtenção de genótipos mais produtivos (Castro et al, 2010). Todavia, além da produtividade, deve-se ressaltar também a qualidade organoléptica e nutricional dos frutos.…”
Section: Introductionunclassified